2020
DOI: 10.1016/j.breast.2020.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Digital analysis of distant and cancer-associated mammary adipocytes

Abstract: Adipocytes and cancer-associated adipocytes (CAAs) are poorly investigated cells in the tumor microenvironment. Different image analysis software exist for identifying and measuring these cells using scanned hematoxylin and eosin (H&E)-stained slides. It is however unclear which one is the most appropriate for breast cancer (BC) samples. Here, we compared three software (AdipoCount, Adiposoft, and HALO®). HALO® outperformed the other methods with regard to adipocyte identification, (> 96% sensitivity and speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Considering that BMI is inaccurate in describing the adiposity of specific fat depots, we also assessed mammary adipocyte size as alternative measure of mammary adiposity. In line with our previous work 22 , we showed a correlation between BMI and adipocyte size, although it is moderate. As for BMI, we found that adipocyte size (area and diameter) is a positive predictor of anti-proliferative response, showing that patients with larger distant adipocytes were more likely to have an anti-proliferative response.…”
Section: Discussionsupporting
confidence: 93%
“…Considering that BMI is inaccurate in describing the adiposity of specific fat depots, we also assessed mammary adipocyte size as alternative measure of mammary adiposity. In line with our previous work 22 , we showed a correlation between BMI and adipocyte size, although it is moderate. As for BMI, we found that adipocyte size (area and diameter) is a positive predictor of anti-proliferative response, showing that patients with larger distant adipocytes were more likely to have an anti-proliferative response.…”
Section: Discussionsupporting
confidence: 93%
“…In the obesogenic state, adipose tissue hypertrophy can lead to adipocyte stress and death, ultimately triggering inflammation. Adipose tissue inflammation is histologically recognized when macrophages engulf dead or dying adipocytes, forming a crown‐like structure (CLS) 11 . The presence of CLS is indicative of inflammation in white adipose tissue (WAT) 2,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Adipose tissue inflammation is histologically recognized when macrophages engulf dead or dying adipocytes, forming a crown‐like structure (CLS) 11 . The presence of CLS is indicative of inflammation in white adipose tissue (WAT) 2,11 . In breast and squamous cell carcinomas of the tongue, WAT inflammation represented by CLS not only correlates with multiple cardiometabolic disorders such as hyperlipidemia, hypertension, and diabetes, but also has a negative impact on progression‐free survival 6,12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…What should be the role of the surrounding and breast cancer-associated adipocytes? A few studies suggest that cancer-associated adipocytes can also cause resistance to radiotherapy and to chemotherapeutic drugs ( 209 , 210 ). Another study described that interaction between cancer-associated adipocytes and cancer cells seems to be more pronounced in obese patients ( 211 ).…”
Section: Future Challenges In Lipid Metabolism and Breast Cancer Trea...mentioning
confidence: 99%